Improved Anti-Collision Algorithm for Tag Identification in Future Internet of Things - Moshref, Mahmoud (International journal of computer network and information security, 2017)
The most important research in the world in these days, research that looking at the internet of thing's (IoT) topics and their applications. Most of these applications depend on RFID system, which includes RFID readers and tags. The important issues in RFID system or network are how we can reduce anti-collision between readers to identify and read tags data. In these paper, we suggest an Improved anti-collision protocol, which can be used to connect RFID readers with RFID tags and reduce the number of RFID tag's collisions. The simulation shows that an Improved Class-1 Generation 2 algorithm is better than Slotted Aloha, Class-1 Generation-2 (Number of Tags Known), Class-1 Generation-2 (Number of Tags Unknown) algorithms.